Use of an ELISA system for detection of equine herpesvirus 1 (EHV-1) antibodies in non-symptomatic pregnant mares and neonatal foals - R. Carvalho; L.M.F. Passos; A.M.G. Gouvea; M. Resende; A.S. Martins; G.C. Franco (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2000)
An ELISA system was applied to study the prevalence of EHV-1 in vaccinated and non-vaccinated Brazilian horses. Serum samples were taken from non-symptomatic pregnant mares, before and after the parturition, and from their neonatal foals. The antigen was prepared from a purified virus fraction (HVE-1 AB1 strain). The ELISA absorbance of 0.3516 was determined as the threshold of negative values. This cut-off level was defined from a selected interval, which determined a sensibility of 100% and a specificity of 94.7%, from a serum collection obtained from pregnant mares and fetuses. In this study, a strong correlation was found between the ELISA and serum neutralization for specific EHV-1 antibody detection.